The role of information in assessing the risk of conducting bankruptcy proceedings - Michał Baran; Kinga Bauer (Risks, 2021)
Modern management means making managerial decisions in many situations-including the administrative ordering of matters of a bankrupt enterprise. The situation in which the court approves the opening of bankruptcy proceedings is strictly regulated by law. This does not mean, however, that such a decision is made under conditions of certainty as to its consequences. The risk of making a wrong decision has significant consequences for everyone who is interested in it (the bankrupt company, its partners, employees, banks, the tax office). The purpose of this article is to explain the importance and significance of the various types of information that are used to reliably assess the value of a failing enterprise's assets. The information of individual types is analyzed in the decision-making process which leads to the right decision on whether to start bankruptcy proceedings. Therefore, in the theoretical part, the authors prepare a list of types of information used in the mentioned process. Then the authors present the results of a survey (103 specialists in the field of bankruptcy), which allows to assess the real meaning of information of individual types. The main contribution for which the present paper is responsible is the description of the verified tool which functioned in the form of the survey that was applied in the study and the result arising from conducting it. This survey was used to achieve the main objective that was focused on constructing the hierarchy of significance of different types of information relating to the risk of conducting bankruptcy proceedings. The main findings show that in general insolvency specialists prioritize the information (financial and also not financial) not originating from financial reporting.
Keywords: 330; bankruptcy proceedings; information management; risk management; sustainability